SUBALTERN SOCIETY CONFLICT IN THE NOVEL “RIJAAL FII ASY-SYAMS” BY GHASSAN KANAFANI BASED ON THE PERSPECTIVE OF GAYATRI CHAKRAVORTY SPIVAK - Heni Subdatul Khafidzoh; Khoirul Anas (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Abstract: This article aims to describe forms of subaltern society conflict in the novel, identify factors of subaltern society conflict in the novel, and understand the impacts of subaltern society conflict in the novel. This article used qualitative and descriptive research. In analyzing the data, the researchers read and understand the novel and then record the required data, including the forms, factors, and impacts of subaltern society conflict on individuals, families, and society. This study produced several data, namely: (1) forms of subaltern society conflict in the novel are cornered, to be demeaned, forced to marry, slander, rude treatment, castration, and smuggling; (2) factors of subaltern society conflict in the novel are questioned, a sneer, harassment, and social inequality; (3) impacts of subaltern society conflict in the novel are: a) individual in the form of feeling concerned, feeling humiliated, unable to express desire, angry at himself, not accepting the situation, stranded in the desert, death, deprived, and discarded; b)society in the form of sickness and fear.